Changing trade and freight distribution intensities : city logistics and rural development - Mishra, Sandeep Kumar; Kolář, Petr; Martínez, Felipe; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
Master's thesis, "Changing trade and freight distribution intensities: city logistics and rural development" is categorized into two parts: first, identified the current ongoing issues in the urban area associated with freight transportation vehicles and provide the solutions to the policymakers of the logistics providers, and to the administrators for obtaining the economic benefits with the reduction of social cost. And second, identified the ongoing issues in the rural area and provide solutions to the policymakers for rural development. Quantitative analysis has been conducted based on the identified factor's weight, volume, distance, and freight value for policymaking, where weight, volume, and distance are independent variables and freight value is the dependent variable.
Vedoucí práce: Petr Kolář
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses